Impact of Climate Change on Crop Water Requirement in Kamala River Basin of Nepal - Dawadi, Sarita; Mishra, Yogendra; Lamichhane, Manoj; Tamrakar, Jebin (Advances in Engineering and Technology: An International Journal, 2022)
The future climate which has crucial role of any hydrological events that occurs within basin will have more uncertainty. Changing the climatic variables, the water balance of the basin will more unpredictable. Not only will climatic parameter changes but also adversely affected the water management within the basin. In this study, an attempt has been carried out to compare the future River flow of Kamala basin and future water demand of Kamala irrigation command area. The CROPWAT and AQUACROP model, based on climatic, soil and crop data, was used to estimate the future Crop Water Requirement (CWR), Irrigation Water Requirement (IWR) and Biomass yield. The hydrological station, because not exist within basin, was not possible to simulate the future river flow of the Kamala basin using any hydrological model. Therefore, the WECS method is simply used to forecast the future monthly flow of Kamala River. The two emission scenarios, ssp245 and ssp585 were conducted based on cropping intensity 170% and 300 % and IWD for each sub-scenario over 12 months was estimated. For the first sixth months, IWR is increased in the future period as maximum and minimum temperature increases and the IWR for monsoon season is less required due to increases in precipitation and again for the post-monsoon season, IWR is increased compared as historical IWR. The highest irrigation water requirement occurs in March month under ssp245 and ssp585 and CI 300%. Whereas, July and August months have the lowest irrigation water demand under ssp245 and ssp585 scenarios. Based on the finding, the production of crop with irrigation system has higher than rainfed system. For paddy, the rainfed system produced dry yield of 6.58 ton/ha whereas, dry yield of irrigated field has 7.05 ton/ha. The future river flow is insufficient to meet the irrigation water demand in first five months in near future under both ssp245 and ssp585 scenarios. The magnitude of deficiency in ssp585 is comparatively higher than in ssp245. As a result, all of these findings suggest that the crop water requirement of KIP is insufficient in the future to provide a year-round irrigation system.